Problems of formation and development of societal constitutionalism in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2023)
This article explores the challenges and complexities surrounding the formation and development of societal constitutionalism in the Republic of Kazakhstan, a nation with a rich historical tapestry and a diverse society. Situated at the crossroads of Europe and Asia, Kazakhstan’s pursuit of constitutionalism transcends domestic boundaries and holds global significance. The historical context sets the stage, delving into the enduring legacies of the Soviet era and the transformative journey from independence to nation-building. These historical junctures have profoundly influenced Kazakhstan’s political identity and its approach to constitutionalism. Examining the legal framework, we uncover how constitutional revisions and ambiguities in legal protections impact the stability of Kazakhstan’s constitutional order. The article then delves into sociopolitical factors, including limited civic engagement, media freedom, and political pluralism, shedding light on the challenges faced by civil society and political diversity. The international dimension emerges as a crucial influencer, with organizations like the United Nations and the OSCE actively promoting democratic governance and constitutionalism. Bilateral relations, regional dynamics, and economic partnerships further shape Kazakhstan’s commitment to align with global norms. As Kazakhstan navigates these challenges and opportunities, it stands at a crossroads, requiring a multifaceted approach to nurture societal constitutionalism. Leveraging its unique position and history, Kazakhstan can contribute to the global discourse on democratic governance and constitutionalism,ultimately reflecting the aspirations of its people. Key words: civil, constitutional law, freedom, legality, stability.